Analysis of Time Periodicity of Sand Cyclone Flushing for Reduce Sand Impurities at Palm Oil Mill Clarification Stations - Renjani, Rengga Arnalis; Syahputra, Ridho Kukuh; Safitri, Lisma; Dharmawati, Nuraeni Dwi (Universitas Brawijaya, 2026)
Palm oil mills used sand cyclones to reduce the sand content in sludge. High sand content (>5% in samples) and low efficiency caused pipe erosion, potential damage to decanter machines, increased maintenance costs, and reduced equipment lifespan. This study aimed to analyze the impact of flushing periodicity on the sand content in the sand cyclone outputs and to determine the optimal flushing periodicity. The experiment was conducted with six flushing time variations (P0 to P5) tested on sand cyclone 1 (SC1) and sand cyclone 2 (SC2). For SC1: P0 had a flushing time of 3.75 minutes, while P1, P2, and P3 were set at 4.25 minutes, and P4 and P5 at 4.75 minutes. For SC2, P0 had 7.50 minutes, P1 was 7.00 minutes, P2 was 7.50 minutes, P3 was 8 minutes, P4 was 7.50 minutes, and P5 was 8.00 minutes. Each treatment was replicated six times. The observed parameters included flushing water requirement, residual oil content, emulsion, moisture content, non-oil solids (NOS), and sand content. The results indicated that flushing periodicity significantly affected flushing water consumption, residual oil levels, emulsion formation, moisture content, NOS, and sand separation. The optimal flushing periodicity was able to reduce sand content in the sand cyclone overflow to 2.50%. To achieve maximum efficiency, a flushing frequency of 15 times per hour with a duration of 4.25 minutes is required for SC1, while for SC2 a flushing frequency of 8 times per hour with a duration of 7.50 minutes is required.